Leveraging microenvironmental synthetic lethalities to treat cancer - Metcalf, Kevin J. (J Clin Invest, 2021)
Treatment resistance leads to cancer patient mortality. Therapeutic approaches that employ synthetic lethality to target mutational vulnerabilities in key tumor cell signaling pathways have proven effective in overcoming therapeutic resistance in some cancers. Yet, tumors are organs composed of malignant cells residing within a cellular and noncellular stroma. Tumor evolution and resistance to anticancer treatment are mediated through a dynamic and reciprocal dialogue with the tumor microenvironment (TME). Accordingly, expanding tumor cell synthetic lethality to encompass contextual synthetic lethality has the potential to eradicate tumors by targeting critical TME circuits that promote tumor progression and therapeutic resistance. In this Review, we summarize current knowledge about the TME and discuss its role in treatment. We outline the concept of tumor cell–specific synthetic lethality and describe therapeutic approaches to expand this paradigm to leverage TME synthetic lethality to improve cancer therapy.